The factorial structure of cognitive abilities in childhood - Ana Azevedo Martins (European Journal of Education and Psychology, 2016)
Recent studies have shown contradictory evidence regarding cognitive abilities differentiation and organization in childhood. Cattell’s investment theory postulated that during the early stages of life, the individual begins with a single and general ability (fluid intelligence), in which the relevance tends to decrease during adolescence, due to the appearance of differentiated abilities developed through the process of socialization and associated with the motivations, interests and experiences. This study analyses whether the factorial structure of the results in a battery of tests supports the existence of a general factor or, instead, a structure formed by different specific factors. A sample of 472 Portuguese children, aged between 4 and 10 years old, completed the Cognitive Competencies Scale for Children (ECCOs 4/10),and four subtests of the Wechsler Intelligence Scale for Children-Third Edition (WISC-III) and Wechsler Preschool and Primary Scale of Intelligence --- Revised (WPPSI-R). The adjustment of some models that reflect different psychometric theories of intelligence was tested by several confirmatory factor analyses (CFA). The implications of the tested models in the organization of ognitive abilities for cognitive development and school learning in childhood are also discussed.